UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI MEDIA PERMAINAN KARTU BERGAMBAR PADA SISWA KELAS 1 SD NEGERI 105407 PEMATANG KEDAH - Sonya Restauli Simatupang; Sutarini; Sujarwo; Sukmawarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low initial reading ability and lack of learning motivation of first-grade students of SD Negeri 105407 Pematang Kedah. The purpose of this classroom action research (CAR) is to determine the effectiveness and improvement of students' reading ability through standardized picture card game media. The subjects of this research are first-grade students of SD Negeri 105407 Pematang Kedah with the indicator of success of the action set if at least 70% of students achieve Minimum Learning Completeness (KBM). The research was conducted in two cycles (Cycle I and Cycle II). The results of the research in Cycle I showed an increase, but had not yet reached the success criteria with an average student activity score of 67%. After improvements in the action and media refinement in Cycle II, the results obtained experienced a significant increase. The average student activity score in Cycle II reached 88%, qualifying as "very good," exceeding the success indicator (70% of the KBM). Therefore, it can be concluded that the use of picture card games has proven effective and has successfully improved the reading skills and learning motivation of first-grade students at SD Negeri 105407 Pematang Kedah.